Immbolization of lipase on multi-walled carbon nanotubes - Alkhatib, Ma'an; Salleh, Hamzah; Sultan, Anans M. (2008)
Immobilized enzymes, such as lipases, have diverse applications including chemical, fuel, pharmaceutical and food processing industries. In this study, commercially available lipase extracted from Aspergillus niger has been immobilized on (MWNTs). The enzyme was bound to carbon nanotubes by covalent bonding, in the presence of N-(3-dimethylaminopropyl)-N'-ethyl)-carbodiimide (EDC) as a coupling reagent. Carbon nanotubes were carboxylated by sonication in 1 M nitric acid prior to treatment with the coupling reagent. Native lipase showed an activity of 2.22 x 10-3 U, whereas, immobilized lipase demonstrated an activity of 0.335 x 10-3, retaining 55 % of the native activity given that only 27.4 % enzyme immobilization has been achieved. One unit is defined as 1nmol of p-nitrophenol released by the hydrolysis of the substrate 4-nitrophenyl palmitate (pNPP) per 1 ml per minute.